2017
DOI: 10.1111/1440-1681.12747
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms of claudin‐1 with small vessel vascular dementia

Abstract: The most recent hypothesis of the development of small vessel vascular dementia (VaD) emphasises the role of blood-brain barrier (BBB) dysfunction. It is hypothesised that certain genetic polymorphisms of the BBB tight junction claudin-1 protein, in combination with adverse environmental risk factors, increase the risk of BBB dysfunction and small vessel VaD. In this case-control study, 97 control participants, with a mean Mini Mental State Exam (MMSE) score of 29.1, and 38 VaD participants were recruited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Claudins play an important role in organizing tight junctions between endothelial cells. Polymorphisms of CLDN1 (claudin1) were recently associated with small vessel vascular dementia [18]. Further supporting a previous study indicating that claudin expression profile alone was able to segregate Alzheimer's disease cases from normal aging and from vascular dementia patients [19].…”
Section: Polymorphisms and Vascular Dementiasupporting
confidence: 75%
“…Claudins play an important role in organizing tight junctions between endothelial cells. Polymorphisms of CLDN1 (claudin1) were recently associated with small vessel vascular dementia [18]. Further supporting a previous study indicating that claudin expression profile alone was able to segregate Alzheimer's disease cases from normal aging and from vascular dementia patients [19].…”
Section: Polymorphisms and Vascular Dementiasupporting
confidence: 75%
“…CLDN1 is a 17 kb gene that codes for a 3.4 kb transcript which translates to an important protein CLDN1 [25]. It has been reported that polymorphisms in CLDN1 are associated with the risk of cancer [14], small vessel vascular dementia [26], leukoaraiosis [27], and hepatitis C virus infection [28,29]. In Hahn-Strömberg V’s study, they found that CLDN1 rs9869263 genotype was related to risk of colon cancer and polymorphisms in CLDN7 were associated with differentiation and age of colon cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that claudin-1 overexpression compensated for BBB dysfunction only in the acute phase of injury. In addition to this, genetic polymorphisms in claudin-1 have been shown to contribute to small vessel vascular dementia (Srinivasan et al, 2017). Claudin-3 is involved in BBB induction and maintenance through signaling via the Wnt/β-catenin pathway (Polakis, 2008), while claudin-5 restricts the entrance of molecules up to 800 Da (Morita et al, 1999).…”
Section: Anatomical Structurementioning
confidence: 99%